Application of extracts of seaweed, NP’SZnO and microorganisms on the plant biomass in tomato - Morales-Meléndez, Raúl; Betancourt-Galindo , Rebeca; Juárez-Maldonado , Antonio; Hernández-Pérez, Armando; González-Fuentes , José Antonio; Puente-Urbina, Bertha; Méndez-López, Alonso (Ecosistemas y Recursos Agropecuarios, 2023)
Agriculture faces serious challenges that demand the production of a greater amount of food for present and future generations, coupled with this, biotic and abiotic factors increasingly affect crop yields, given this problem, biostimulants are an alternative. The aim of this study was to determine the effect of foliar application of seaweed extract (EA = 0, 500, 2 500 ppm) and zinc oxide nanoparticles (NP’SZnO = 0, 50 and 250 mg L−1) and coinoculation of the substrate with rhizospheric microorganisms (without microorganisms [SMos] and with microorganisms soaked in the substrate [CMos = 10 spores mL−1 of Glomus intraradices and 1x106 CFU of Azospirillum brasilense]) on the accumulation of biomass in tomato plants. The experiment was established under a randomized block design with a factorial arrangement (3x3x2), with eight repetitions. The analysis of variance identified significant differences between the treatments, the factors analyzed and the respective interactions. EA sprays improved stem dry weight (PST), stem biomass (BT) and root biomass (BR); while, spraying with NP’SZnO increased root fresh weight (PFR), leaf dry weight (PSH), root dry weight (PSR), leaf biomass (BH) and BR; whereas, the co-inoculation of the soil with microorganisms (CMos) improved the fresh leaf weight (PFH), PSR and BR. The application of biostimulants showed a stimulating effect on the vegetative growth of tomato plants.